2018
DOI: 10.1111/pala.12385
|View full text |Cite
|
Sign up to set email alerts
|

Diets of giants: the nutritional value of sauropod diet during the Mesozoic

Abstract: A major uncertainty in estimating energy budgets and population densities of extinct animals is the carrying capacity of their ecosystems, constrained by net primary productivity (NPP) and its digestible energy content. The hypothesis that increases in NPP due to elevated atmospheric CO 2 contributed to the unparalleled size of the sauropods has recently been rejected, based on modern studies on herbivorous insects that imply a general, negative correlation of diet quality and increasing CO 2. However, the nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 103 publications
1
11
1
Order By: Relevance
“…The detection of cycad–cycadophyte leaf fragments in the cololite slides, and only a trace of conifer leaves on the slides, is contrary to previous prediction of diet choice for large herbivorous dinosaurs (although based on sauropods, animals much larger than Borealopelta ), which argued against cycads and favoured araucarian leaves based on the energetics of their digestion [ 12 , 110 ]. Adult sauropods, however, would have accessed trees, whereas Borealopelta would have accessed low-stature plants.…”
Section: Discussioncontrasting
confidence: 89%
“…The detection of cycad–cycadophyte leaf fragments in the cololite slides, and only a trace of conifer leaves on the slides, is contrary to previous prediction of diet choice for large herbivorous dinosaurs (although based on sauropods, animals much larger than Borealopelta ), which argued against cycads and favoured araucarian leaves based on the energetics of their digestion [ 12 , 110 ]. Adult sauropods, however, would have accessed trees, whereas Borealopelta would have accessed low-stature plants.…”
Section: Discussioncontrasting
confidence: 89%
“…However, the fact that predation did not entirely alleviate competitive interactions between the megaherbivores suggests that theropods may have favoured feeding on small or young individuals 11,67,154 . Finally, elevated atmospheric CO 2 levels during the Late Cretaceous would have enhanced terrestrial primary productivity 155158 , potentially reducing competitive strain among herbivores. In light of these considerations, the finding that both megaherbivorous mammals and dinosaurs were similarly resource-limited, despite their different evolutionary histories, physiologies, and exposure to otherwise very different conditions, is remarkable.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the possibility of feathers (or their analogous and homologous structures) being present in the closely related pterosaurs 122 might imply an even earlier synapomorphic acquisition of a tachymetabolic condition, eventually lost in later diverging clades like Sauropoda. The reason for such secondary loss is unknown but could possibly be due to trophic constraints (e.g., unrealistic foraging habitat range requirements for a purported endothermic sauropod population), [123][124][125][126] observations that can be tested by future discoveries and further study. Regardless of the thermophysiological implications, our study suggests that no or exceedingly few sauropod occurrences will ever be found in polar palaeolatitudes outside of warm-house or hot-house intervals.…”
Section: Articlementioning
confidence: 99%